Corrigendum to ‘Enhancing compressive behavior of concrete with novel low-cost hybrid passive confinement including large rupture strain cotton ropes: Experimental findings and a design-oriented model’ [Case Stud. Constr. Mater. 21 (2024) e03496] (Case Studies in Construction Materials (2024) 21, (S2214509524006478), (10.1016/j.cscm.2024.e03496)) - Saingam, Panumas; Hussain, Qudeer; Ejaz, Ali; Nawaz, Adnan; Joyklad, Panuwat; Khan, Kaffayatullah (My University, 2024)
The authors regret that the fifth author's name was incorrect in the published article. The correct name of the fifth author as “Panuwat Joyklad” The acknowledgement section should be updated by including the last line in the acknowledgement. The revised acknowledgement should read as: This research is a result of the project entitled “Development of a Novel, Low-cost and High Performance Hybrid FRP Composites for Waste Aggregate Concrete for Sustainable Cities Grant NO.RE-KRIS/ FF67/023” by King Mongkut's Institute of Technology Ladkrabang (KMITL), which has been received funding support from the NSRF. The APC was funded by King Mongkut's Institute of Technology Ladkrabang Research Fund. The authors would like to apologise for any inconvenience caused. DOI of original article: < https://doi.org/10.1016/j.cscm.2024.e03496>